2012
DOI: 10.1007/s00595-012-0397-0
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene mesh repair of incarcerated and strangulated hernias: a prospective clinical study

Abstract: The findings revealed effective and safe usage of mesh along with antibiotic therapy in patients undergoing incarcerated and strangulated hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…Although the wound complication rate may be increased with bowel resection, the mesh never required removal. 28,29 Bessa and Abdel-Razek 30 analyzed the combined results of prosthetic mesh repair in cases of strangulated inguinal and incisional hernias available in the literature. Combined analysis of 572 patients revealed that bowel resection was required in 14.7% of cases, with a wound infection rate of 4%, seroma rate of 3.8%, and mesh infection in 1 patient (0.2%).…”
Section: Emergent Prosthetic Repair Of Acutely Strangulated Herniasmentioning
confidence: 99%
“…Although the wound complication rate may be increased with bowel resection, the mesh never required removal. 28,29 Bessa and Abdel-Razek 30 analyzed the combined results of prosthetic mesh repair in cases of strangulated inguinal and incisional hernias available in the literature. Combined analysis of 572 patients revealed that bowel resection was required in 14.7% of cases, with a wound infection rate of 4%, seroma rate of 3.8%, and mesh infection in 1 patient (0.2%).…”
Section: Emergent Prosthetic Repair Of Acutely Strangulated Herniasmentioning
confidence: 99%
“…At present, the use of a mesh for the tension-free repair of an emergency hernia does not seem to be an absolute contraindication 11 . A mesh is safe to apply even in cases of intestinal resection and anastomosis 10,[17][18][19][20] . Evidence has accumulated regarding the application of synthetic meshes, and clinicians recommend the use of synthetic meshes to repair FHs in patients, including in emergency situations 2,10,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, irreducible hernias could be obstructed or strangulated hernias or none of them (Onuigbo and Njeze, 2016). High recurrence rates are the most debatable problems in repair of incarcerated and strangulated hernias without mesh (5-21 %) and high wound infection rates (6-14 %) (Topcu et al, 2013). The rate of surgical site infection (SSI) following hernia repair using mesh ranges from 0% to 14%.…”
Section: Introductionmentioning
confidence: 99%